Genetic variants of increased waist circumference in psychosis. (December 2017) - Hukic, Dzana S.; Ösby, Urban; Olsson, Eric; Hilding, Agneta; Östenson, Claes-Göran; Gu, Harvest F.; Ehrenborg, Ewa; Edman, Gunnar; Schalling, Martin; Lavebratt, Catharina; Frisén, Louise
Abstract : Objective: We examined whether established metabolic risk genetic variants in the population confer a risk for increased waist circumference in patients with schizophrenia spectrum disorders and also an association with schizophrenia spectrum disorders irrespective of waist circumference. Patients and methods: We analyzed the association in (i) a case–case model in which patients with schizophrenia spectrum disorder with increased waist circumference (≥80 cm for women and ≥94 cm for men) ( n =534) were compared with patients with normal waist circumference (<80 cm for women; <94 cm for men) ( n =124), and in (ii) a case–control model in which schizophrenia spectrum disorder patients with increased waist circumference or irrespective of waist circumference were compared with population-derived controls ( n =494) adjusted for age, sex, fasting glucose, smoking, and family history of diabetes. Results: Genetic variants in five genes ( MIA3, MRAS, P2RX7, CAMKK2, and SMAD3 ) were associated with increased waist circumference in patients with schizophrenia spectrum disorder ( P <0.046). Genetic variants in three other genes ( PPARD, MNTR1B, and NOTCH2 ) were associated with increased waist circumference in patients when compared with control individuals ( P <0.037). Genetic variants in the PPARD, MNTR1B, NOTCH2, and HNF1B were nominally associated with schizophrenia spectrum disorder irrespective of waist circumference ( P <0.027). No differences in waist circumference between specific psychosis diagnoses were detected. Conclusion: Increased waist circumference in patients with schizophrenia spectrum disorder may be explained, in part, by increased metabolic risk gene burden, and it indicates a shared genetic susceptibility to metabolic disorder and psychosis per se . Along these lines, common metabolic risk genetic variants confer a risk for increased waist circumference in patients with schizophrenia spectrum disorders.